KOORDINASI DALAM KOLABORASI ANTAR STAKEHOLDERS PENGEMBANGAN DESA WISATA JUNGSEMI KECAMATAN KANGKUNG KABUPATEN KENDAL - Diah Farah Fauziah; Retna Hanani; Kismartini Kismartini (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
The development of Tourism Villages in Kendal Regency is currently progressing, supported by the vision and mission of the Kendal Regent, which are to realize Kendal Reliable, Superior, Prosperous and Equitable and focus on four pillars of development, namely Industry, Tourism, MSMEs, and Generation 4.0. Jungsemi Village is one of the tourist villages located in the coastal area of Kendal Regency whose development is being intensified by the government. The success of Jungsemi tourism village development does not only come from one actor. Collaboration between stakeholders is needed to optimize the implementation of development in the tourism sector. The existence of less harmonious relationships and sectoral egos between stakeholders in the coordination process makes the reason for the importance of this research. This research aims to analyze coordination between stakeholders and analyze the supporting and inhibiting factors of coordination in the development of Jungsemi Tourism Village. This research uses a qualitative descriptive method with data collection through observation, interviews, and documentation. The results showed that the coordination carried out by stakeholders in the development of Jungsemi Tourism Village has been running dynamically, which is characterized by changes and progress in tourism management. However, the competence of stakeholders owned by Karang Taruna is still low. The agreement and commitment in coordination owned by the Pokdarwis, private sector, and the community are also not optimal. The lack of knowledge in the field of tourism and the low human resources of the community have not become the carrying capacity of the tourism village to develop. Supporting factors consist of unity of action, communication, and division of labor, while discipline is an inhibiting factor. Suggestions are to provide socialization and motivation, increase commitment, hold sustainable collaboration, coordinate through proactive communication, and increase understanding of tourism awareness.